2001
DOI: 10.1159/000051774
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosing Pemphigus foliaceus: A Retrospective Analysis of Clinical, Histological and Immunological Criteria

Abstract: Background: Clinical, histological and immunological criteria distinguish pemphigus foliaceus (PF) from pemphigus vulgaris (PV), but whether and how often they are concordant in the same patient is unknown. Methods: Seven clinical records were selected from two hospital settings for having a diagnosis of PF and the initial serum and histopathological specimens still available. Controls were 8 PV records selected in the same way. Histopathological slides were re-evaluated. Stored sera were studied by indirect i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
1
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 9 publications
1
16
1
3
Order By: Relevance
“…Following up these cases we found that all of them proved positive also in IIF in the further course of the disease. We do not understand such a difference in the IIF results of our study and that of Delmonte et al [1] since both our groups used monkey oesophagus as a substrate. Histopathology is useful for the differentiation of PV and PF; however, it cannot replace a highly reliable DIF method.…”
contrasting
confidence: 94%
See 1 more Smart Citation
“…Following up these cases we found that all of them proved positive also in IIF in the further course of the disease. We do not understand such a difference in the IIF results of our study and that of Delmonte et al [1] since both our groups used monkey oesophagus as a substrate. Histopathology is useful for the differentiation of PV and PF; however, it cannot replace a highly reliable DIF method.…”
contrasting
confidence: 94%
“…
We read with interest the paper by Delmonte et al [1] on the histological and immunological criteria for diagnosing pemphigus foliaceus (PF). Since our experience in this field is quite different, we would like to present our findings.
…”
mentioning
confidence: 99%
“…[13] Delmonte et al reported raised anti-Dsg 1 antibody in 62% of PV. [14] In a Thai study, anti-Dsg 1 and Dsg 3 antibodies were found in 85.7% and 100% cases respectively in PV while in Iranian patients they were detected in 76.7% and 94.5% patients respectively. [15,16] In PF, both mean anti-Dsg1 and 3 titers were high in our study.…”
Section: Discussionmentioning
confidence: 99%
“…PV was confirmed by histology at presentation. Repeat biopsies would have strengthened the evidence for transition to PF as one study reported that the absence of mucosal erosions could not differentiate PF from PV reliably and that histological criteria for PF had to be fulfilled for the diagnosis of PF [13]. One PV patient in that study had antibodies to Dsg1 and Dsg3 on immunoblotting but only anti-Dsg1 antibodies were present unequivocally on Dsg ELISA testing (the anti-Dsg3 ELISA value was in the ‘gray zone’).…”
Section: Discussionmentioning
confidence: 99%